2008
DOI: 10.2174/138161208785740036
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System and Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a neurodegenerative disease that is characterised by repeated inflammatory/demyelinating events within the central nervous system (CNS). In addition to relapsing-remitting neurological insults, leading to loss of function, patients are often left with residual, troublesome symptoms such as spasticity and pain. These greatly diminish "quality of life" and have prompted some patients to self-medicate with and perceive benefit from cannabis. Recent advances in cannabinoid biology are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 154 publications
(350 reference statements)
0
22
0
Order By: Relevance
“…There are evidences that the therapeutic effect of 9 THC on the experimental autoimmune encephalomyelitis (EAE) model of MS is achieved through an inhibition of glutamate release . The 9 THC is suggested to have a neuroprotective function in MS, counteracting the glutamate-mediated excitotoxicity; again, this effect is accomplished via the activation of CB1 receptors (Fujiwara and Egashira, 2004;Jackson et al, 2005;Baker and Pryce, 2008;Cabral and Griffin-Thomas, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are evidences that the therapeutic effect of 9 THC on the experimental autoimmune encephalomyelitis (EAE) model of MS is achieved through an inhibition of glutamate release . The 9 THC is suggested to have a neuroprotective function in MS, counteracting the glutamate-mediated excitotoxicity; again, this effect is accomplished via the activation of CB1 receptors (Fujiwara and Egashira, 2004;Jackson et al, 2005;Baker and Pryce, 2008;Cabral and Griffin-Thomas, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the endogenous cannabinoid system and cannabinoid receptors have become the target of several studies aiming to investigate the potential relevance of cannabinoids in the MS management. Clinical and experimental research demonstrated that the endocannabinoid system is altered in MS and that it partially acts via cannabinoid receptors CB1 and CB2 (Baker et al, 2001;Centonze et al, 2007;Baker and Pryce, 2008;Rossi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to ameliorating the clinical symptoms in animal models (Baker and Pryce, 2008) and MS patients (Rog, 2010), cannabinoids are also being recognized for their ability to control disease progression (de Lago et al, 2010). Although much progress has been achieved over the last several decades, questions still remain regarding the protective mechanisms of various cannabinoids and the involvement of CB1 and CB2 receptors.…”
Section: Discussionmentioning
confidence: 99%